Remarks on Mortgage Certificate Institute - Tchitanava, Nato (European Scientific Journal, ESJ, 2017)
The presented article deals with the importance of mortgage certificate and the circumstances hindering its use in practice that very often occur in private law relations. Namely this determines topicality of the given issue. In 2007 amendments were made in the civil legislation of Georgia to simplify procedures of assignment of mortgage ensured claim. In particular, legal norms regulating the mortgage certificate were established. However, the mortgage certificate institute could not manage to find its niche in the private law relations. As a result, the norms regulating the mortgage certificate in legislative acts carry only informative character. Comparativelegal analysis of the abovementioned legal norms enables us to determine the reasons why establishment of Legal norms regulating mortgage certificate failed in 2007. Alongside with this, it is anticipated that there will be interpretations of legislative changes necessary for putting mortgage certificate into practice. It will also clarify goals and results of simultaneous existence of mortgage certificate and registry extract, possibility of replacement mortgage certificates with registry extracts.